2020
DOI: 10.1155/2020/7050356
|View full text |Cite
|
Sign up to set email alerts
|

Design and Multiobjective Optimization of Magnetorheological Damper considering the Consistency of Magnetic Flux Density

Abstract: The consistency of magnetic flux density of damping gap (CMDG) represents the balancing magnetic flux density in each damping gap of magnetorheological (MR) dampers. It can make influences on the performances of MR dampers and the accuracy of relevant objective functions. In order to improve the mechanical performances of the MR damper with a two-stage coil, the function for calculating CMDG needs to be found. By establishing an equivalent magnetic circuit model of the MR damper, the CMDG function is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…that is, if one objective function was improved, another objective function reduction is required as the cost; hence, solutions A and B of the multiobjective optimization problem were called noninferior solutions or Pareto optimal solutions. e Pareto optimal solution was a set in which each Pareto optimal solution was only a noninferior solution, and the multiobjective optimization problem searched for these Pareto optimal solutions [47].…”
Section: Optimal Layout Methods For Mr Dampersmentioning
confidence: 99%
“…that is, if one objective function was improved, another objective function reduction is required as the cost; hence, solutions A and B of the multiobjective optimization problem were called noninferior solutions or Pareto optimal solutions. e Pareto optimal solution was a set in which each Pareto optimal solution was only a noninferior solution, and the multiobjective optimization problem searched for these Pareto optimal solutions [47].…”
Section: Optimal Layout Methods For Mr Dampersmentioning
confidence: 99%
“…response surface method [16][17][18], tolerance constraints [19], dynamical system constraints [20], and b-spline constraints [21]), and slower convergence (e.g. genetic algorithms [22][23][24][25] and their derivative algorithms NSGA-II [26] and NSGA-III [27,28]). These constraints increase processing complexity and make satisfying asymmetry and other performance measures difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the mechanical performance of multicoil MR damper, the damping force and dynamic range were the optimization goals, and the external geometric 1 size of the damper was used as a constraint variable to optimize the internal geometrical size of the MR damper. 7,8 Zhang et al 9 proposed a new type of pumped MR damper, and used a fast multi-objective genetic algorithm to optimize the structural parameters. The results showed that the optimized MR damper can improve dynamic performance and heat dissipation performance.…”
Section: Introductionmentioning
confidence: 99%